A rare case of angiofibroma of the mandible: A case report - Mohammed Israr Ul Khaliq; Ajaz A. Shah; Nahida Dar (Elsevier, 2016)
Angiofibroma is a rare, highly vascular nonencapsulated tumor, which is locally invasive. A rare case of angiofibroma of the mandible in a 16-year-old female patient is reported here. The lesion was excised along with surgical removal of right mandibular third molar tooth. Patient was followed up for 1 year without any recurrence.